Babesia divergens in human in Gansu province, China - Jinming Wang; Shangdi Zhang; Jingqiong Yang; Junlong Liu; Dekui Zhang; Youquan Li; Jianxun Luo; Guiquan Guan; Hong Yin (Emerging Microbes and Infections)
Human babesiosis is an important tick-borne infectious disease. We investigated human babesiosis in the Gansu province and found that it is prevalent in this area with a prevalence of 1.3%. Results of gene sequencings indicate that 1.3% of patients were positive for Babesia divergens. This initial report of human B. divergens infections in Gansu Province should raise awareness of human babesiosis.